Mineralogical analysis of plutonic and volcanic rocks at selected slope sections of the Kuala Lumpur-Karak Highway - Khairulazman, Nurul Afiffah; Jelani, Jestin; Suif, Zuliziana; Umor, Mohd Rozi; Azmi, Nur Anati; Md Yusof, Zainuddin; Ahmad, Nordila; Abd Halim, Abd Akram Haikal; Rosle, Qalam A’zad (Universitas Mercu Buana, 2025)
The Kuala Lumpur-Karak Highway (KL-KH) is a key route connecting Kuala Lumpur to the East Coast states of Peninsular Malaysia. It passes through three distinct geological formations: the Kuala Lumpur Granite, Genting Sempah Complex, and Bentong Raub Suture Zone. These formations feature unique rock mineral compositions and microstructures that influence the strength and behavior of rock masses. This study used X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) to analyze the mineralogical properties of plutonic and volcanic rock samples from the highway. The plutonic sample from KM29 (GKM29) consists of quartz, muscovite, and albite, while the volcanic sample from KM93 (LKM93) is rhyolite, containing quartz, albite, muscovite, and biotite. While both samples share similar minerals, they differ in texture, mineral proportions, and carbon content. The GKM29 sample has a more granular texture, while the LKM93 sample is finer. These differences in mineral composition and texture affect the mechanical properties of the rocks, including strength and durability, which are crucial for slope stability. Understanding these variations is essential for assessing slope stability and potential geological hazards along the highway. This study emphasizes the importance of early geological assessments for effective slope management and road safety, enabling better planning and maintenance strategies.